Antibacterial Effect of Juglans regia, Citrus sinensis, Vicia faba, and Urtica urens Extracts under In vitro Conditions - Ali Khakpour; Negar Ahmadi Shadmehri; Hanif Amrulloh; Hamed Kioumarsi (Pandawa Institute, 2023)
Various agricultural products are known to have anti-microbial, anti-cancer, and anti-inflammatory effects. As we can mention, Walnut (Juglans regia) husk, orange (Citrus sinensis) peel, Broad bean (Vicia faba) peel, and Nettle (Urtica urens) are proven to have antimicrobial and anticancer actions. Also, plant diseases such a Pectobacterium carotovorum, Ralstonia solanacearum, Dickeya chrysanthemi, and Pseudomonoas syringae are known to cause annual damage to plant products. Therefore, in the current study, the researchers evaluated their antibacterial activity on the mentioned bacteria under in vitro conditions. Extracts of J. regia husk, C. sinensis peel, V. faba outer peel and U. urens were prepared by maceration method and their anti-bacterial activity on P. carotovorum, D. chrysanthemi, P. syringae, R. solancearum was evaluated using blank disk and well diffusion to obtain minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values. J. regia (husk) and V. faba (outer peel) extracts revealed an anti-bacterial effect on all 4 studied bacteria, while C. sinensis (peel) only inhibited the growth of P. syringae and U. urens only had this effect on P. syringae and R. Solancearum. The inhibition zones varied from 8 to 14 mm, while almost all MIC and MBC rates were 6.25 and 12.5 mg/mL, respectively. Based on the antimicrobial results, the extracts that showed suitable antibacterial effects on certain bacteria can be further studied to be used as natural pesticides.